La production médiatique de l’espace public et sa médiation du politique - Martine Paquette (Communication)
The counterpart to the increasing popularity of the concept of public space echoes not only the plurality of its uses, but also the difficulties in its conceptualization and operationalization. This article is attached to the multidisciplinary foundation of public space and throws buoys for reflection on its double dimension, political and mediated. The author suggests that the representation of the universe of social relations be regarded in relationship with that which underlies the political regulation of each form of the modern State and that the historical transformations of the mediatized public space be approached from this angle. The article also approaches mediatization as a form of mediation that tends to polarise the diversity of mediations and examines the sense given to the terms space and public.